Clinicopathologic correlations in a family with a TBK1 mutation presenting as primary progressive aphasia and primary lateral sclerosis. Issue 7 (2nd October 2019) - Hirsch-Reinshagen, Veronica; Alfaify, Omar A.; Hsiung, Ging-Yuek R.; Pottier, Cyril; Baker, Matt; Perkerson, Ralph B.; Rademakers, Rosa; Briemberg, Hanna; Foti, Dean J.; Mackenzie, Ian R.
Abstract: Mutations in the TANK binding kinase 1 gene ( TBK1 ) are associated with amyotrophic lateral sclerosis and/or frontotemporal dementia; however, the range of clinical phenotypes and neuropathological changes associated with these mutations have not yet been completely elucidated. We present the detailed clinical, neuroimaging, and neuropathological features of two brothers carrying the TBK1 p.Gly272_Thr331del mutation. Both presented with very similar and unusual clinical features including primary progressive aphasia and asymmetric-onset primary lateral sclerosis (PLS). Repeated electrophysiological studies failed to reveal any lower motor neuron involvement. Neuropathological evaluation of both cases revealed frontotemporal lobar degeneration with TDP-43 proteinopathy type B and selective involvement of upper motor neurons with TDP-43 inclusions. The stereotypical clinical presentation and neuropathological findings in these cases widen the phenotypic spectrum of TBK1 mutations and provide insights into the pathogenesis of PLS.